Infezione da virus dell'epatite E nel suino e nell'uomo: aggiornamento sulle metodiche diagnostiche di laboratorio - Dell'Amico, Maria Chiara <1970> (Alma Mater Studiorum - Università di Bologna, 2009)
The first part of the thesis is a brief review on the most important aspects of HEV infection in human and swine, followed by an update on the laboratory techniques currently in use for the diagnosis of HEV infections in humans and animals. The second part refers on the results of two investigations carried out on the presence of HEV infection in swine farms in Toscana and Piemonte and on the presence of HEV infection in pigs and humans in some rural communities in Bolivia. HEV strains isolated from swine herds in Toscana and Piemonte were all included in the genotype 3, showing particular homology with Dutch porcine isolates, Spanish porcine and human isolates and British human isolates. The investigation carried out, with a random sampling, in the province of Cuneo, detected HEV infection with a prevalence of 46% on farms with a number of pigs greater than 500. HEV was detected in pigs and humans in rural communities in Bolivia and all the viral isolate were included in the genotype 3. Aminoacidic homology of human and swine isolates was estimated to be 92%. Results on the development of a Real Time RT-PCR to detect HEV are also reported. The used Real Time RT-PCR protocols, one step and two steps, exhibited good sensitivity to detect several Italian swine HEV strains with high rate of genetic variability.